Aktivitas Antimikroba Ekstrak Laos Putih (Alpinia Galangas) Terhadap Bakteri Escericia Coli Dan Salmonella Sp. - Lely Adel Violin Kapitan (JURNAL INFO KESEHATAN, 2017)
A study was conducted on antibacterial activity of white Laos ethanol extract (Alpinia galanga S) on the growth of Escherichia coli bacteria and Salmonella sp bacteria. The white Laos ethanol extract used was a white Laos ethanol extract obtained by extraction with 70% ethanol solvent using percolation method. The effectiveness of white laos ethanol extract was tested by a diffusion method using cylinder. The antibacterial activity of the white Laos ethanol extract is known by observing a drag zone in the clear region around the cylinder, then measured using a sliding range. The experiment used Completely Randomized Design with 5 treatments and 3 replications. The data obtained were then analyzed statistically using analysis of variance (ANOVA). The results showed that the value of F Table 1% <F Count. Subsequent tests using the Honest Real Difference Test (BNJ) showed a diversity coefficient of 0.51% <5% indicating there was a marked difference between each treatment being tested. From these results, it can be concluded that the extract of white Laos ethanol has antibacterial activity against the growth of Escherichia coli bacteria starting at 25% concentration with 10.45 mm2 inhibitory zone and Salmonella sp bacteria starting at 25% concentration with 17,45 mm2 inhibit zone. The higher the concentration the wider the barrier zone.